MIMO Lowly Damped System: Free-Free Vibrations of an Aluminium Tooling Plate. Issue 28 (2015) - Pintelon, R.; Rolain, Y.
Abstract: Real life problems are always more complicated than expected. What is thought to be a generalised output error stochastic problem (known input, noisy output observations) of a linear system operating in open loop is often an errors-in-variables stochastic problem (noisy input, noisy output observations) of a nonlinear system operating in feedback. In addition, for lowly damped systems a "large" data set can still be "short" compared with the length of the impulse response of the system. The free-free vibrations of an aluminium tooling plate presented in this benchmark problem combine all these difficulties. The benchmark data are available at the IFAC TC1.1 repository http://tc.ifac-control.org/1/1/Data%20Repository.